Longitudinal Analysis of Adiponectin through 20-Year Type 1 Diabetes Duration - Tamara J. LeCaire; Mari Palta (Journal of Diabetes Research)
Little information exists on the trajectory and determinants of adiponectin, a possible insulin sensitizer and marker for inflammation and endothelial function, across the duration of type 1 diabetes. The Wisconsin Diabetes Registry Study followed an incident cohort ≤30 years of age when diagnosed with type 1 diabetes during 1987–1992 up to 20-year duration. Adiponectin was concurrently and retrospectively (from samples frozen at −80°C) measured for those participating in a 20-year exam (n=304), during 2007–2011. Adiponectin levels were higher in females, declined through adolescence, and increased with age thereafter. Lower levels were associated with greater body weight and waist circumference and with higher insulin dose, especially at longer diabetes durations. Higher levels were associated with higher HbA1c and, at longer durations, with higher albumin-creatinine ratio. Adiponectin levels showed consistency within individuals that was not explained by these factors. We conclude that markers for insulin resistance are associated with lower adiponectin, and markers for potential microvascular complications are associated with higher adiponectin. The previously reported relationship with HbA1c remains largely unexplained. Additional individual specific factors likely also influence adiponectin level. The relationship between adiponectin and urinary protein excretion may enable identification of those predisposed to kidney disease earlier in type 1 diabetes.